Labour market adjustments in Europe and the US: how different? - Beyer, Robert; Smets, Frank (Frankfurt am Main, 2015)
"We compare the labour market response to region-specific shocks in Europe and the US and to national shocks in Europe and investigate changes over time. We employ a multi-level factor model to decompose regional labour market variables and then estimate the dynamic response of the employment level, the employment rate and the participation rate using the region-specific variables and the country factors. We find that both in Europe and the US labour mobility accounts for about 50% of the long run adjustment to region-specific labour demand shocks and only a little more in the US than in Europe, where adjustment takes twice as long. In Europe labour mobility is a less important adjustment mechanism in response to country-specific labour demand shocks that cause stronger and more persistent reactions of the employment and the participation rate. However, we detect a convergence of the adjustment processes in Europe and the US, reflecting both a fall in interstate migration in the US and a rise in the role of migration in Europe. Finally, we show that part of the difference between Europe and the US in previous studies may be due to the use of different data sources."